Group guidance services to improved creativity for teachers - Solihatun, Solihatun; Aminudin, Djoni; Evitarini, Anggia (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2017)
Creativity in the learning process by teachers is very important in order to support the task at school. Teacher creativity allows teachers to apply various learning methods that encourage students interest to learn from the classroom. Besides, creativity for teachers is needed to support student development. This study aims to determine the level of creativity of teachers through group guidance services. Subjects in this study involved 10 teachers at Gemma Insani Indonesia Depok. Data analysis used a quantitative approach with pre-test and post-test control group of one design. The results show effective group guidance to improve teacher creativity at Gemma Insani Indonesia Depok.